Mitochondrial Sirtuin 4 Resolves Immune Tolerance in Monocytes by Rebalancing Glycolysis and Glucose Oxidation Homeostasis - Tao, Jie; Zhang, Jingpu; Ling, Yun; McCall, Charles E.; Liu, Tie Fu (Frontiers in Immunology, 2018)
The goal of this investigation was to define the molecular mechanism underlying physiologic conversion of immune tolerance to resolution of the acute inflammatory response, which is unknown. An example of this knowledge gap and its clinical importance is the broad-based energy deficit and immunometabolic paralysis reported in blood monocytes from non-survivors of human and mouse sepsis that precludes sepsis resolution. This immunometabolic dysregulation is biomarked by ex vivo endotoxin tolerance to increased glycolysis and TNF- expression. To investigate how tolerance switches to resolution, we adapted our previously documented models associated acute inflammatory, immune, and metabolic reprogramming that induces endotoxin tolerance as a model of sepsis in human monocytes We report here that mitochondrial sirtuin 4 (SIRT4) physiologically breaks tolerance and resolves acute inflammation in human monocytes by coordinately reprogramming metabolism and bioenergetics. We find that increased SIRT4 mRNA and protein expression during immune tolerance counters the increase in pyruvate dehydrogenase kinase 1 (PDK1) and SIRT1 that promote tolerance by switching glucose-dependent support of immune resistance to fatty acid oxidation support of immune tolerance. By decreasing SIRT4, PDC reactivation rebalances mitochondrial respiration and by decreasing SIRT1, SIRT4 increases fatty acid synthesis. The precise mechanism for the mitochondrial SIRT4 nuclear feedback is unclear, by our findings are consistent with a new concept in which mitochondrial SIRT4 directs the axis that controls anabolic and catabolic energy sources.